Response of immunoglobulin M in gut mucosal immunity of common carp (Cyprinus carpio) infected with Aeromonas hydrophila - Mu, Qingjiang; Dong, Zhaoran; Kong, Weiguang; Wang, Xinyou; Yu, Jiaqian; Ji, Wei; Su, Jianguo; Xu, Zhen (Frontiers in Immunology, 2022)
Immunoglobulin (Ig) M is an important immune effector that protects organisms from a wide variety of pathogens. However, little is known about the immune response of gut mucosal IgM during bacterial invasion. Here, we generated polyclonal antibodies against common carp IgM and developed a model of carp infection with Aeromonas hydrophila via intraperitoneal injection. Our findings indicated that both innate and adaptive immune responses were effectively elicited after A. hydrophila infection. Upon bacterial infection, IgM+ B cells were strongly induced in the gut and head kidney, and bacteria-specific IgM responses were detected in high levels both in the gut mucus and serum. Moreover, our results suggested that IgM responses may vary in different infection strategies. Overall, our findings revealed that the infected common carp exhibited high resistance to this representative enteropathogenic bacterium upon reinfection, suggesting that IgM plays a key role in the defense mechanisms of the gut against bacterial invasion. Significantly, the second injection of A. hydrophila induces strong local mucosal immunity in the gut, which is essential for protection against intestinal pathogens, providing reasonable insights for vaccine preparation.